A CRITICAL READING OF LUMEN GENTIUM - Cortina Canceran, Delfo (Asian Horizons, 2015)
This paper delves on the Lumen Gentium (LG) of the Vatican II documents of the church. It focuses on the tensions found in the text which basically contain a duality of perspectives. These perspectives revolve around ecclesiological models of the church. In particular, the mystical body of Christ and the people of God models, the people of God and the hierarchical institution perspectives are prominent. Moreover, the paper will defend the democratization models that address the main problem of the church, which is power. These democratization models side with the victims of this unilateral and asymmetrical power — the poor and women — for their liberation.